Quantitative determination of zopiclone tablets «Sonovan» by spectrophotometry - S. L. Zagorodniy; S. O. Vasyuk (Zaporozhye State Medical University, 2014)
Aim. A new spectrophotometric method of assay zopiclone based on its interaction with bromtymol blue in acetone solution and measuring the absorption of the reaction product in the visible spectrum at a wavelength of 400 nm. Methods and results. The method used to quantify dimedrol in dosage forms - tablets «Sonovan». The basic characteristics validated by the State Pharmacopoeia of Ukraine. Conclusion. According to the obtained experimental data, the technique can be correctly reproduced and is suitable for use in pharmaceutical and forensic analytical laboratories.